Digital educational technology on LGBT-phobic bullying for school-aged adolescents - Mariana Mercês Mesquita Espíndola; Ednaldo Cavalcante de Araújo; Adrian Thaís Cardoso Santos Gomes da Silva; Danilo Martins Roque Pereira; Marclineide Nóbrega de Andrade Ramalho; Thainara Torres de Oliveira; Weslla Karla Albuquerque Silva de Paula; Josueida de Carvalho Sousa (Revista Brasileira de Enfermagem, 2025)
ABSTRACT Objectives: to develop a digital educational technology on LGBT-phobic bullying, in the form of a comic book, for health education among school-aged adolescents. Methods: a methodological study employing the Planning of Computer-Supported Learning Activities method to guide the organization of development stages, combined with Edgar Morin’s pedagogical framework, under the perspective of comprehension, health education, and the context of sexual and gender diversity. Results: the comic book “LGBT-Phobic Bullying: Shall We Talk?” was developed with the aim of contributing to education and awareness in the fight against LGBT-phobic bullying in school environments, serving as a health educational technology product. Final Considerations: as a contemporary approach, this technology was designed to address a sensitive topic in adolescent LGBTQIAP+ health in a reflective manner. The combination of visual storytelling in comics with educational messages can effectively contribute, alongside educational practices, to reducing stigma, prejudice, bullying, and other forms of violence against LGBTQIAP+ adolescents.